2016
DOI: 10.1108/gm-11-2014-0105
|View full text |Cite
|
Sign up to set email alerts
|

Supervisor support and work engagement of hotel employees in Malaysia

Abstract: Purpose – This study aims to examine the impact of supervisor support and to assess the moderating role of gender on employee work engagement in the context of the Malaysian hospitality industry. Design/methodology/approach – Data were collected from a sample of 438 customer-contact employees in Malaysian upscale hotels and tested using the partial least squares technique. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 73 publications
2
26
0
4
Order By: Relevance
“…Cenkci and Özçelik (2015) have examined the moderating effect of a leader's gender on the relationship between leadership style and employees' work engagement, similarly finding that there is no gender difference in the relationship. On the other hand, Suan and Nasurdin (2016) have investigated the moderating effect of employees' genders on the relationship between supervisor support and work engagement and found that the positive effect of supervisor support on work engagement is stronger for male than female employees.…”
Section: Gender Differences In Career Development and Work Engagementmentioning
confidence: 99%
“…Cenkci and Özçelik (2015) have examined the moderating effect of a leader's gender on the relationship between leadership style and employees' work engagement, similarly finding that there is no gender difference in the relationship. On the other hand, Suan and Nasurdin (2016) have investigated the moderating effect of employees' genders on the relationship between supervisor support and work engagement and found that the positive effect of supervisor support on work engagement is stronger for male than female employees.…”
Section: Gender Differences In Career Development and Work Engagementmentioning
confidence: 99%
“…provides training participants with a feeling that supervisors care about them and value their contribution to work outcomes. Based on social exchange theory (Blau 1964) and perceived organisational support (Eisenberger et al 1986), several authors have argued that this affective attachment is positively related to individual work outcomes (Golden and Veiga 2008;Knies and Leisink 2014) and relieves the effects of work-related stress (Eschleman 2011;Suan and Nasurdin 2016). At the team level, the effect of emotional supervisor support may be even stronger because interactions between team members give rise to the collective perception of supervisor support through repeated cycles of individual interactions and influence (Pohl and Galletta 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Supervisor support is defined as the extent to which employees perceive their supervisor's interest in their well-being and job performance (Maertz et al, 2007). Prior studies have investigated the moderating effect of supervisor support (Muhammad and Hamdy, 2005;Ru Hsu, 2011;Choi et al, 2012;Chauhan et al, 2017) on job satisfaction (Zhang et al, 2019), stress, burnout, training, work engagement (Demerouti et al, 2001;Schaufeli et al, 2008;Ling Suan and Nasurdin, 2016;. These studies have shown that supervisor support can have powerful effects on employees.…”
Section: The Moderating Role Of Supervisor Supportmentioning
confidence: 99%